Effect of β-sitosterol on Insulin Receptor, Glucose Transporter 4 Protein Expression and Glucose Oxidation in the Gastrocnemius Muscle of High Fat Diet Induced Type -2 Diabetic Experimental Rats - Krishnan, Madhan; Babu, Shyamaladevi; Rajagopal, Ponnulakshmi; Nazar, Sohara Parveen; Chinnaiyan, Mayilvanan; Jayaraman, Selvaraj (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The newly available medications are ineffective because of their unintended side effects in the treatment of type 2 diabetes. Hence, search drugs, from plant sources. β-sitosterol is plant sterols with structurally almost like that of cholesterol. It is widely present in various medicinal plants. Although the sterol it was shown to possess antihyperglycemic activity, the mechanism of action of the plant sterol on a high-fat diet (HFD)-induced insulin resistance in gastrocnemius muscle is not yet determined. Objectives: To the assessment of the beneficial role of β-sitosterol on the expression of insulin‑signaling molecules within the skeletal muscle of HFD-fed and sucrose‑induced type‑2 diabetic rats. Materials and Methods: The effective oral β-sitosterol dose (20 mg/kg of body weight) was administered once daily until the conclusion of the research period. (30 days post‑induction of diabetes) to HFD- fed diabetic rats. At the end of a period of experiment, fasting blood sugar (FBG), oral glucose (OGT) and tolerances (IT), Homeostasis Model Assessment for Insulin Resistance (HOMA-IR) and Quantitative Insulin Sensitivity Check Index (QUICKI), serum lipid profile, lipid peroxidation (LPO), peroxide (H2O2) and hydroxyl (OH*) generation, antioxidant enzymes as well as the levels of insulin signaling molecules like insulin receptor (IR), glucose transporter subtype 4 (GLUT4) proteins and glycogen concentration within the gastrocnemius muscle were assessed. Results: A diabetic rat indicates impaired tolerances for glucose and insulin and molecules signaling insulin (IR and GLUT4) proteins and glycogen concentration. In diabetic rats, serum insulin, lipid profile, LPO, H2O2, OH* has been found to be increased. The β-sitosterol treatment stabilized altered blood glucose levels, serum insulin levels, lipid profile, markers of oxidative stress, IR and GLUT4 protein levels. Conclusion: Our current findings suggest that β-sitosterol enhances Glycemic regulation in the gastrocnemius muscle by IR and GLUT4 activation of HFD- fed and sucrose‑induced type‑2 diabetic rats.
Keywords: β-sitosterol; IR; GLUT4; Glucose uptake and oxidation; Gastrocnemius muscle; High fat diet and sucrose; Type-2 diabetes; Insulin Signaling; Insulin resistance